2015
DOI: 10.3109/10903127.2015.1076094
|View full text |Cite
|
Sign up to set email alerts
|

Lights and Siren Transport and the Need for Hospital Intervention in Trauma Patients

Abstract: Emergent ambulance transportation is associated with increased risk of collision, injury, and death for EMS professionals, patients, and the general public. Time saved using lights and siren (L&S) is typically small, and often provides minimal clinical benefit. Our objective was to investigate the frequency of L&S transports, describe the precision of the decision to employ L&S to predict the need for a time critical hospital intervention (TCHI) within 15 minutes of hospital arrival, identify clinical predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…4,5,[11][12][13][14][15] Where controversy remains is whether the timed saved is clinically significant, with many of these studies concluding that it generally was not. Most published studies demonstrate a variable, but statistically significant, reduction in response/transport.…”
Section: Reportmentioning
confidence: 99%
“…4,5,[11][12][13][14][15] Where controversy remains is whether the timed saved is clinically significant, with many of these studies concluding that it generally was not. Most published studies demonstrate a variable, but statistically significant, reduction in response/transport.…”
Section: Reportmentioning
confidence: 99%
“…Although, the Danish healthcare system is free, some patients bypass the dispatch system or public prehospital transport, and arrive on their own accord. In contrast to other diseases as trauma [25], cardiac arrest [26, 27], acute myocardial infarction [28] and stroke [29, 30], septic patients, to a lesser extent, arrived by public prehospital transport. In our study, part of the explanation for patients arriving without public pre-hospital transport could be the short distances with low traffic load.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the time saved -a couple of minutes -is considered moderate, with no clinical benefit demonstrated to date [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have applied a more comprehensive approach, using the application of time-critical hospital intervention (TCHI) as an endpoint to indicate the appropriateness of LST [2,9,10,15]. TCHI is defined as those procedures or treatments that are urgently needed, requiring skills or devices that are either not available or cannot be properly performed in the prehospital setting [2,8,10]. Recent studies have demonstrated that up to a quarter of life-threatening situations, such as airway obstruction, severe dyspnoea, hemodynamic instability and abnormal Glasgow Coma Scale, require TCHI [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation